Plasticity in root system architecture of rice genotypes exhibited under different soil water distributions in soil profile. (2nd October 2019) - Kano-Nakata, Mana; Nakamura, Tomomichi; Mitsuya, Shiro; Yamauchi, Akira
ABSTRACT: The root system architecture (RSA) has been reported to be determined by several root traits such as branching, elongation, and growth angle. This study aimed to evaluate the genotypic variation of plasticity in RSA in response to different soil water distributions in a soil profile. IR64 (shallow root system), YTH183 (adapted to rainfed lowland conditions due to high plasticity in root elongation), and Kinandang Patong (KP – deep root system) were grown in PVC root boxes for 34 days under continuously waterlogged conditions and with soil moisture fluctuations (SMF). For SMF, watering was done from the top of the root box (TI-SMF) or from the bottom of the root box (BI-SMF). A water gradient was observed more clearly in BI-SMF than in TI-SMF, while mean soil moisture content in the root box was kept at around 23% (v/v) after first irrigation in both SMF treatments. RSA changed drastically with SMF in all cultivars, all of which tended to shift root distribution to deeper soil layers in response to SMF. Such changes in RSA resulted from different degrees of plasticity exhibited mainly in nodal root and L-type lateral root development. YTH183 showed a greater ability to change its root growth angle and thus its root distribution in the deeper soil layer compared to IR64 and KP under SMF, indicating that YTH183 could help to improve RSA in cultivars adapted to SMF.